(untitled) (BIRDEM Medical Journal, 2018)
Idiopathic hypereosinophilic syndrome is characterized by prolonged peripheral blood eosinophilia neither clonal nor secondary to an identifiable cause and eosinophil mediated organ dysfunction, most frequently involving the heart, the central or peripheral nervous system and the lungs. Here, we report a 22-year-old woman who presented with severe abdominal pain due to pancreatitis. On subsequent work-up, she was found to have idiopathic hypereosinophilic syndrome. It is an unusual presentation of idiopathic hypereosinophilic syndrome, which prompted to report this case. Birdem Med J 2018; 8(3): 260-262